2017
DOI: 10.1134/s0006297917070070
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli signal peptidase recognizes and cleaves archaeal signal sequence

Abstract: Tk1884, an open reading frame encoding α-amylase in Thermococcus kodakarensis, was cloned with the native signal sequence and expressed in Escherichia coli. Heterologous gene expression resulted in secretion of the recombinant protein to the extracellular culture medium. Extracellular α-amylase activity gradually increased after induction. Tk1884 was purified from the extracellular medium, and its molecular mass determined by electrospray ionization mass spectrometry indicated the cleavage of a few amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…E. coli signal peptidase cleaved the signal peptide consisting of 26 amino acids [22]. Here we demonstrate the effect of truncation of signal peptide on the secretion of Tk1884.…”
Section: Separation Of Intracellular Cytosolic and Membranous Fractionsmentioning
confidence: 64%
See 1 more Smart Citation
“…E. coli signal peptidase cleaved the signal peptide consisting of 26 amino acids [22]. Here we demonstrate the effect of truncation of signal peptide on the secretion of Tk1884.…”
Section: Separation Of Intracellular Cytosolic and Membranous Fractionsmentioning
confidence: 64%
“…We have previously produced Tk1884, an α-amylase from hyperthermophilic archaeon T. kodakarensis, with the native signal sequence in E. coli and demonstrated that signal peptidase of the host cleaved the signal sequence of the archaeal origin and the mature protein was secreted in the extracellular medium [22]. In the present study we have shown that deletion of the sixteen N-terminal amino acids, out of twenty six, of the signal peptide resulted in the secretion of the recombinant protein to the extracellular medium but without cleavage of the signal peptide.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports on production and extracellular secretion of recombinant bacterial enzymes produced in E. coli, including α-amylase (Shahhoseini, 2003;Yamabhai et al, 2008;Malik et al, 2013), chitinase (Yamabhai et al, 2008); mannanase (Zhang et al, 2006), subtilisin (Ikemura et al, 1987) and xylanase (Jalal et al, 2011). Apart from bacterial enzymes, production and secretion of archaeal enzymes, using their native signal peptide, have also been reported in E. coli (Muhammad et al, 2017). We have previously cloned the TK0522 gene encoding the mature carbohydrate esterase from Thermococcus kodakarensis and characterized the recombinant protein (Tariq et al, 2019).…”
mentioning
confidence: 99%